EFFECT OF STEAM PRESSURE AND TEMPERATURE ON THE AMOUNT OF OIL PRODUCED IN A CITRONELLA OIL DISTILLATION MACHINE - Zainuri Anwar; Ahmad Imam Rifa'i; Almas Nurzain (Universitas Muhammadiyah Semarang, 2023)
One of the parameters that affect the citronella oil distillation process is the pressure and temperature of the steam. The aim of this research was to determine the optimal working pressure and temperature for the distillation process. The distillation method uses the direct steam type, by varying the pressure in the boiler, namely 2 bar, 2.5 bar and 3 bar. Steam temperature increases with increasing working pressure, namely 100 - 110ºC. The raw material for citronella used 5 kg with a long distillation process of 4 hours. The test results showed that the highest amount of oil and yield occurred at a pressure of 3 bar and a temperature of 110ºC, 19 ml and 0.32%, respectively. The color of the oil produced pale yellow to brownish yellow with a specific gravity of oil at 25ºC which is 0.878 gr/ml. Citronella oil has good quality according to the SNI 06-3953-1995 citronella oil quality standards.